Breast Feeding and Melatonin: Implications for Improving Perinatal Health - Anderson, George; Vaillancourt, Cathy; Maes, Michael; J. Reiter, Russel (Journal of Breastfeeding Biology, 2016)
The biological underpinnings that drive the plethora of breastfeeding benefits over formula-feeding is an area of intense research, given the cognitive and emotional benefits as well as the offsetting of many childhood- and adult-onset medical conditions that breast-feeding provides. In this article, we review the research on the role of melatonin in driving some of these breastfeeding benefits. Melatonin is a powerful antioxidant, anti-inflammatory and antinociceptive as well as optimizing mitochondrial function. Melatonin is produced by the placenta and, upon parturition, maternal melatonin is passed to the infant upon breastfeeding with higher levels in night-time breast milk. As such, some of the benefits of breastfeeding may be mediated by the higher levels of maternal circulating night-time melatonin, allowing for circadian and antioxidant effects, as well as promoting the immune and mitochondrial regulatory aspects of melatonin; these actions may positively modulate infant development. Herein, it is proposed that some of the benefits of breastfeeding may be mediated by melatonin's regulation of the infant's gut microbiota and immune responses. As such, melatonin is likely to contribute to the early developmental processes that affect the susceptibility to a range of adult onset conditions. Early research on animal models has shown promising results for the regulatory role of melatonin.
Keywords: breastfeeding; melatonin; gut microbiota; formula feed; sudden infant death syndrome; infancy.